Protection of mice against experimental infection wild Brucella abortus strain by vaccination via oral and intraperitoneal routes with Brucella abortus RB51 - Waffa A Ahmed; AL-Gburi Nagham M.; Sanaa Lwis (Mirror of Research in Veterinary Sciences and Animals, 2016)
The study was designed to detect the effect of an oral and intraperitoneal (I/P) immunization of mice with B. Abortus RB51 to protect mice against a wild strain of B. abortus I/P challenge infection. Three groups of mice were used in this study. The first group (1st G) immunized with 108 *2 CFU of B. Abortus RB51 intraperitoneally (I/P). The second group (2nd G) immunized orally with 108 *2 CFU dose (Ten minutes prior immunization, all mice were drenched with 0.2 ml of 10% sodium bicarbonate to neutralize gastric acidity). Whereas, the third group (3rdgroup) inoculated with 0.2 ml phosphate buffer saline (PBS) and acted as the control group. The results indicated that there was a significant difference (P<0.05) in antibody titer at 5th week in the I/P group and in the 3rd week in oral group, while there was no significance between the two route through all the periods. However, after the challenge, the antibody titer raised to 0.84±0.11 and 1.14±0.11 in the two route and control group in 3rd and 7th day post challenge respectively. The Ab titer reached 1.44±0.11 in the I/P route and remain at 1.14±0.11 in oral and control at 10th day/post-challenge. The oral inoculation gave a mild infection, which was cleared at 5th week after infection, and it induced a humoral response. However, I/P challenge gave moderate infection, which was cleared at 6th week after infection. Wild B. Abortus was isolated at a lowest level after the challenge from internal organs, in animals immunized I/P compared with the other two groups. In conclusion, I/P and oral immunization were able to give protection against the virulent wild strain B. abortus in mice. Besides, the probability of these mice in transmitting the vaccine to other animals was low and vaccine was safety in pregnant vaccinated mice.